RANCANG BANGUN BUCK BOOST CONVERTER PADA PHOTOVOLTAIC UNTUK POMPA AIR MOTOR DC KOLAM IKAN - Naufal Farkhan Muflikh; riny sulistyowati (Universitas Nusa Cendana, 2025)
Solar energy plays an important role in reducing dependence on fossil fuels. However, fluctuations in sunlight intensity cause power variations in solar panels. This research aimed to develop a Buck-Boost Converter system to stabilize the voltage on solar panels that could support the operation of water pumps in fish ponds. This system used Arduino-based hardware and control. The researcher conducted research through literature studies, photovoltaic (PV) system design, Buck-Boost Converter circuit, device testing, and data analysis. The researcher used the main components, including 100 Wp solar panels, Buck-Boost Converter, Arduino Uno, INA219 sensor, and DC motor pump. The researcher tested the system for seven days to observe the stability of voltage and power under various lighting conditions. The test results showed that the Buck-Boost Converter could maintain voltage stability with an average power of 56.4 W or about 65.7% of the solar panel capacity. The system efficiently charged the 12V battery to power the water pump. This technology was suitable for environmentally friendly and energy-efficient, renewable energy-based aquaculture applications, with great potential to support the development of renewable energy systems in the aquaculture sector